2012
DOI: 10.1371/journal.pone.0036233
|View full text |Cite
|
Sign up to set email alerts
|

Selective Blockade of Trypanosomatid Protein Synthesis by a Recombinant Antibody Anti-Trypanosoma cruzi P2β Protein

Abstract: The ribosomal P proteins are located on the stalk of the ribosomal large subunit and play a critical role during the elongation step of protein synthesis. The single chain recombinant antibody C5 (scFv C5) directed against the C-terminal region of the Trypanosoma cruzi P2β protein (TcP2β) recognizes the conserved C-terminal end of all T. cruzi ribosomal P proteins. Although this region is highly conserved among different species, surface plasmon resonance analysis showed that the scFv C5 possesses very low aff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
1
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 41 publications
2
1
0
Order By: Relevance
“…A cell invasion assay in the presence of distinct molecules (mAb-10D8, scFv-10D8, and negative controls) was performed to confirm scFv-10D8 function. Accordingly, scFv-10D8 showed a clear capacity to specifically reduce parasite invasion, which is compatible with the results described by Ayub et al [43]. This result was similar to that of the experiment without purified protein.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…A cell invasion assay in the presence of distinct molecules (mAb-10D8, scFv-10D8, and negative controls) was performed to confirm scFv-10D8 function. Accordingly, scFv-10D8 showed a clear capacity to specifically reduce parasite invasion, which is compatible with the results described by Ayub et al [43]. This result was similar to that of the experiment without purified protein.…”
Section: Discussionsupporting
confidence: 92%
“…The scFv expression analysis was performed in a pET22b+ vector, which allowed for the insertion of the pelB leader sequence for assessing expression in the periplasm, which is an environment conducive to the formation of the disulfide bonds that allow the correct conformation of proteins including scFvs [45]. The scFv-10D8 expression levels observed in the periplasm in the present study are consistent with those reported for other scFvs, which are usually low [43,46,47]. Instead of the low level of expression at the periplasm, we were able to show the binding capacity of scFv-10D8 through Western blotting, confirming the same specificity described for mAb-10D8 [48].…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation